2005
DOI: 10.1039/b502122g
|View full text |Cite
|
Sign up to set email alerts
|

Non-trivial behavior of palladium(ii) acetate

Abstract: Reaction of activated palladium metal with a HNO3/acetic acid mixture produces both orange Pd3(OAc)6, 1, and purple Pd3(OAc)5(NO2), 2. Compound has a trinuclear structure derived from that of the well-known triangular complex 1 in which one acetate group has been replaced by a nitrite group which is bonded to one palladium atom by the nitrogen atom and to another Pd atom using one of the oxygen atoms. Highly pure 1 can be made by continuous removal of the nitric oxides from the reaction mixture using a flow of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
87
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(96 citation statements)
references
References 34 publications
8
87
0
1
Order By: Relevance
“…A plausible explanation for this phenomenon is that the commercially available trimeric palladium acetate needs to be activated or dissociated in order to produce the monomeric species required for catalysis. [18] Another explanation could be that the Diels-Alder adduct participates as a ligand in the reaction; this type of activation has been previously suggested for the diacetoxylation of 1,3-dienes. [19] Once the optimum conditions for the transformation were found, we investigated the scope of the procedure, and the results are given in Table 2.…”
mentioning
confidence: 95%
“…A plausible explanation for this phenomenon is that the commercially available trimeric palladium acetate needs to be activated or dissociated in order to produce the monomeric species required for catalysis. [18] Another explanation could be that the Diels-Alder adduct participates as a ligand in the reaction; this type of activation has been previously suggested for the diacetoxylation of 1,3-dienes. [19] Once the optimum conditions for the transformation were found, we investigated the scope of the procedure, and the results are given in Table 2.…”
mentioning
confidence: 95%
“…46 This was closely followed by a 1 H NMR study by Cotton and co-workers, which showed that the trimeric structure (1) is largely retained in methanol, chloroform and benzene. 47 The dipole moment or dielectric constant of a solvent is frequently invoked to describe its polarity, although the two properties are intrinsically different. This can be demonstrated by comparing methanol with NMP, which have markedly different dipole moments, yet very similar dielectric constants (Table 1).…”
Section: Solution Structure Of Pd(oac)mentioning
confidence: 99%
“…16,17 Recently, we found that a complex pattern in the NMR spectrum in C 6 D 6 and CDCl 3 may be attributed to hydrolysis or to the formation of a nitrite derivative that is formed following some of the recently reported preparations for Pd 3 (OAc) 6 . 18 Here we report a reproducible and dependable two-step procedure for the synthesis of trinuclear Pd 3 (OAc) 6 from PdCl 2 . The method proceeds in high yield to produce a crystalline material that is soluble in various organic solvents and that gives a 1 H NMR spectrum with only one acetate resonance.…”
Section: Trinuclear Palladium(ii) Acetatementioning
confidence: 99%